Organic field effect transistors for textile applications. - Bonfiglio, A. (IEEE Transactions on information technology in biomedicine)
In this paper, several issues concerning the development of textiles endowed with electronic functions will be discussed. In particular, issues concerning materials, structures, electronic models, and the mechanical constraints due to textile technologies will be detailed. The idea starts from an already developed organic field-effect transistor that is realized on a flexible film that can be applied, after the assembly, on whatever kind of substrate, in particular, on textiles. This could pave the way to a variety of applications aimed to conjugate the favorable mechanical properties of textiles with the electronic functions of transistors. Furthermore, a possible perspective for the developments of organic sensors based on this structure are described.